An Active-Matrix Organic Light-Emitting Diode Display With Consistent Low-Luminance Levels Regardless of Temperature - Nak-Yoon Kim; Dong-Sup Sim; Chang-Hoon Jeon; Nack-Bong Choi; Han-Wook Hwang; Seung-Woo Lee (IEEE Access, 2024)
This paper proposes a new method that adjusts anode-initialization voltage of light-emitting diodes (OLEDs) depending on temperature to mitigate temperature-sensitive low-luminance inconsistency. Active-matrix OLED displays are increasingly adopting higher refresh rates (HRRs) to ensure fast and smooth image transitions. Experimental studies indicate that ultra-low-luminance-levels (ULLLs) with very low driving currents become more sensitive with rapid anode voltage initialization cycle after applying HRRs. This sensitivity stems from the anode charging slope, intertwined with OLED characteristics. It is important to note that OLED turn-on voltage and current density depend on temperature. To address this, we analyzed the influences of driving currents, refresh rates, and temperature on ULLL expressions. Subsequently, we propose an adjustable anode initialization voltage depending on temperature. The proposed method successfully reduced luminance changes from ~100% to less than 1% over the operating temperature range from 0°C to 50°C.